-(y-3)=2y+6

Simple and best practice solution for -(y-3)=2y+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -(y-3)=2y+6 equation:


Simplifying
-1(y + -3) = 2y + 6

Reorder the terms:
-1(-3 + y) = 2y + 6
(-3 * -1 + y * -1) = 2y + 6
(3 + -1y) = 2y + 6

Reorder the terms:
3 + -1y = 6 + 2y

Solving
3 + -1y = 6 + 2y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2y' to each side of the equation.
3 + -1y + -2y = 6 + 2y + -2y

Combine like terms: -1y + -2y = -3y
3 + -3y = 6 + 2y + -2y

Combine like terms: 2y + -2y = 0
3 + -3y = 6 + 0
3 + -3y = 6

Add '-3' to each side of the equation.
3 + -3 + -3y = 6 + -3

Combine like terms: 3 + -3 = 0
0 + -3y = 6 + -3
-3y = 6 + -3

Combine like terms: 6 + -3 = 3
-3y = 3

Divide each side by '-3'.
y = -1

Simplifying
y = -1

See similar equations:

| 4.50+0.05=0.20x-4.50 | | 4=-8.0n | | x+(26+x)=64 | | 5w^2+12w^2= | | 8(y-1)=3y+17 | | -5k-2k=14 | | -4-9/3=-7 | | -7(n+3)=-34+6n | | 64x^2-192x=0 | | 4.7=30 | | .4*-.03= | | 7x+22=11x+68 | | V-39=-17 | | 3=k+4+5 | | 21x+3=12x+6 | | -(1-7x)=4x-13 | | 2x^2-12x-27=0 | | 5=5-4s-7s | | .4x-.03= | | 3x+x+40=180 | | x-20+2-(-7)=9 | | 3b-5+6b=-5 | | 1/6X-5=-11 | | 11-(8-8n)=8 | | (-16)-(-t)=(-45) | | 4(7y-3)= | | 3(2x+1)-5=10 | | 100n+10n=0n+15n | | -1(-m+n+1)= | | 1/5+1/4x=1/3x+5/6 | | -5=6x+4+3x | | 4/7=11/14x-4/7x |

Equations solver categories